2022
DOI: 10.1002/adom.202201881
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Control of Ultrafast Circular Photon Drag Current in Multilayer PtSe2 Revealed Via Terahertz Emission

Abstract: The generation and control of ultrafast photocurrents on the surface of transition‐metal dichalcogenides (TMDs) are essential for the development of advanced optoelectronic devices. A detailed understanding of the mechanism of ultrafast photocurrent generation is primarily needed to design functional devices. Here, it is reported that ultrafast photocurrents in multilayer PtSe2 are induced by the photon drag effect with high conversion efficiency. Particularly, under circularly polarized laser excitation, anis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…They claimed that, as the proposed technique could be efficient to determine the carrier transport as well as efficient to investigate photon drag current in telecommunication devices. [186] A report demonstrates the ultra-thin flakes of Pt-TMDC-based electronic imprints for next-generation wearable electronics. In this contribution, large-scale synthesis of PtSe 2 and PtTe 2 is achieved through CVD at low temperatures (400 °C).…”
Section: Miscellaneous Applicationsmentioning
confidence: 99%
“…They claimed that, as the proposed technique could be efficient to determine the carrier transport as well as efficient to investigate photon drag current in telecommunication devices. [186] A report demonstrates the ultra-thin flakes of Pt-TMDC-based electronic imprints for next-generation wearable electronics. In this contribution, large-scale synthesis of PtSe 2 and PtTe 2 is achieved through CVD at low temperatures (400 °C).…”
Section: Miscellaneous Applicationsmentioning
confidence: 99%
“…In this regard, polarized terahertz (THz) emission spectroscopy based on ultrafast femtosecond lasers is a powerful optical tool for generating and detecting ultrafast spin photocurrents 24 , 25 . Very recently, THz emission has been observed in centrosymmetric Dirac semimetal PtSe 2 films due to the photon drag effect 26 , 27 and a second nonlinearity from a structural asymmetry 28 . Remarkably, Luo et al 5 observed the light-induced transient phase transition and hence giant photocurrent (i.e., THz emission) in bulk Dirac semimetal ZrTe 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Prior investigations of the nonlinear properties of PtSe2 have been restricted to PtSe2 as a saturable absorber with no demonstrations on the layer dependent nonlinearities 28 . Very recent studies have investigated THz photocurrents in PtSe2 but were limited to a single thickness of 2.4 nm 29 or 50 nm, 30 limiting the understanding of the effect of the bandstructure. Further, these studies have assumed an entirely centrosymmetric nature and neglected the effect of the substrate.…”
Section: Introductionmentioning
confidence: 99%